Analisis Kinerja Produksi dan Faktor-Faktor yang Mempengaruhi Produktivitas Tambang Batubara di PT. XYZ - Andrawina, Andrawina (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
This study aims to analyze production performance and the factors influencing the productivity of mining operations at PT. XYZ during August 2025. The evaluation covers production achievement against the corporate work plan (RKAP) and the owner’s operational plan, equipment availability (Physical Availability), the productivity of loading and hauling units, and various types of loss time that reduce effective working hours. The results indicate that production realization reached only 65% of the RKAP target, while achieving 102% of the owner’s plan for total material. Low equipment availability, high loss time such as no hauler, wait operator, and front preparation, as well as the underperformance of 80-ton and 100-ton units, were identified as the main contributors to production deviation. Additional influencing factors include unit reassignment, suboptimal haul road conditions, and insufficient operational fleet numbers. The study recommends optimizing fleet management, enhancing preventive and predictive maintenance programs, reorganizing hauling workflows, and controlling dominant loss time sources to improve operational efficiency and production target achievement in future periods.